Results in the Latin America and Caribbean Region 2017, Volume 10 - World Bank (World Bank, Washington, DC, 2022)
Latin America and the Caribbean is growing again after being the hardest-hit region during the global deceleration. But to keep making progress on poverty reduction and reducing inequality, the region needs to grow faster and to remain particularly mindful of the tremendous setbacks external shocks can inflict. A series of natural disasters over the last months have been stark reminders of the risks the region faces without further efforts and resources dedicated to ensuring resilience. In the post commodity boom, the good news is that social progress has not been reversed. In fact, all signs are that countries in the region are taking steps to consolidate this progress and ensure that even at lower growth rates, the poor and vulnerable do not suffer. But there is no time to waste. We now know that poverty and inequality reduction as well as middle class growth in Latin America and the Caribbean came to a halt in 2015. What’s more, images of devastation from storms and earthquakes in recent weeks are the latest and powerful reminders that without resilience, we cannot continue advancing. As you will read in the following pages, the World Bank has been at the forefront in helping the region to be proactive on all these fronts. As we highlight some of the projects that reached completion over the past 12 months, we find important recurring themes around the issues of protecting the vulnerable and developing resilience to external shocks such as natural disasters particularly for small states.